(untitled) (International Journal of Scientific Research in Science and Technology, 2025)
Tetrazole-tethered tetrahydrobenzo[b]thiophene-3-carbonitrile derivatives have gained significant attention due to their diverse biological and pharmaceutical applications. In this study, we present an efficient synthesis of tetrazoles using an isocyanide-based multicomponent condensation strategy. The reaction involves a nitrile as precursor, isocyanide, aldehyde, and a sulfur source under optimized catalytic conditions, leading to the formation of highly functionalized frameworks. Furthermore, the cyclization of the nitrile with sodium azide facilitates the introduction of the tetrazole moiety, enhancing the molecular complexity. The developed methodology provides a facile, high-yielding, and sustainable approach to constructing novel heterocyclic scaffolds with potential medicinal relevance.